Education and Training in Revolutionary Ethics for Officers and Party Members in the New Era following Ho Chi Minh's Thought (Práxis Educativa, 2025)
The education and training of revolutionary ethics for cadres and party members, particularly younger members, are vital for the future of any nation. President Ho Chi Minh, a renowned Vietnamese philosopher, emphasized the critical importance of instilling revolutionary ethics in officials and party members to contribute to building a strong, prosperous, and contented Vietnam. The objective of this educational initiative is to foster self-discipline, cultivate personal growth, and train party members in revolutionary ethics in accordance with Ho Chi Minh’s ideology. This approach is rooted in the principle of integrating theory with practice, along with harmonizing.Keywords: Education. Ho Chi Minh. Revolutionary Ethics. Officers. Party Members.